(untitled) (Research, Society and Development, 2020)
The objective was to determine the second-limiting amino acid in diets based on corn-soybean meal for Japanese quails in the growth and laying stages. A total of 1,440 Japanese quails were used in three experiments in phases 1 to 21; 22 to 42 and 85 to 210 days of age, respectively. Each experiment contained eight treatments with six replications of ten birds. The experimental diets were based on corn-soybean meal. The levels of methionine + cysteine ​​were adequate in all experimental diets, but there was variation in the attendance of another second essential amino acid. In experiments 1 and 2, quails that were fed diets with adequate levels of methionine + cysteine ​​and lysine showed higher weight gain (g/bird) and better feed conversion (g/g). Feed intake (g/bird) was not influenced. In experiment 3, adequate levels of all amino acids promoted a lower feed intake (g/bird) and better feed conversion per egg mass (g/g) and per dozen eggs (g/dozen). Egg weight (g), weight (g) and shell thickness (mm) and specific gravity (g/cm3) were not affected. The diets that met the requirements of all amino acids promoted the laying of eggs with a greater weight of albumen (g) and lower weights of egg yolk (g). In conclusion, the second-limiting amino acid in plant diets for Japanese quails is lysine.